1957
DOI: 10.3171/jns.1957.14.3.0285
|View full text |Cite
|
Sign up to set email alerts
|

Possible Factors in the Development of the Arnold-Chiari Malformation

Abstract: NOLD, 2 in 1894, reported on a series of hydrocephalic individuals exhibiting, also, congenital defects in the region of the hindbrain. Although these cases varied considerably, the essential condition was that of a herniation of tongue-like processes of cerebellar tissue into the cervical canal. In 1891 and 1896 Chiari 5,6 described a series of similar cases in which a distorted medulla, as well as cerebellar tissue, was within the cervical canal. In these cases the tongues of cerebellar tissue were so bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

1963
1963
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(62 citation statements)
references
References 13 publications
0
62
0
Order By: Relevance
“…The hydrodynamic theory [17][18][19][20][21], traction theory [22,23], dysgenesis of the hindbrain/ developmental arrest theory [24][25][26][27] and other theories [28][29][30][31][32] a neural tube defect with the Chiari-II malformation; this theory was based on their laboratory experiments. They proposed that the neurulation defect was directly related to and preceded formation of the Chiari-II malformation, and they suggested that the failure to adequately occlude the neurocele led to the failure of distention of the primi tive cranial ventricular system.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrodynamic theory [17][18][19][20][21], traction theory [22,23], dysgenesis of the hindbrain/ developmental arrest theory [24][25][26][27] and other theories [28][29][30][31][32] a neural tube defect with the Chiari-II malformation; this theory was based on their laboratory experiments. They proposed that the neurulation defect was directly related to and preceded formation of the Chiari-II malformation, and they suggested that the failure to adequately occlude the neurocele led to the failure of distention of the primi tive cranial ventricular system.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have shown that there is an inverse relationship between the relative size of the posterior fossa and the degree of tonsillar her niation (r = 0.54, p = 0.0035). A discrepancy between the size of the posterior fossa and the requirements of its growing contents was postulated over 30 years ago by Bar ry et al [23] to explain the more extensive brainstem anomalies that comprise the type-II Chiari malformation seen particularly in association with open neural tube defects. Small posterior fossa size along with anomalies of the skull base have also been demonstrated radiologically in cases of the Chiari-I malformation [ 16.…”
Section: Hindbrain Herniation and Posterior Fossa Sizementioning
confidence: 99%
“…Boyles reported that the volume of the posterior fossa was "highly heritable" (7). Embryologically, the Chiari malformation has been described as a mesodermal deficiency (30) and as a neuroectodermal failure (4,26,27). Gripp, however, proposes that displacement of the cerebellar tonsils may be due to osseous and cartilaginous abnormalities instead of being the result of embryological disturbances (19).…”
Section: █ Discussionmentioning
confidence: 97%